The Maximum Bite Force for Treatment Evaluation in Severely Affected Adult SMA Patients—Protocol for a Longitudinal Study - Kruse, Teresa; Lehmann, Helmar C.; Braumann, Bert; Fink, Gereon R.; Wunderlich, Gilbert (Frontiers in Neurology, 2020)
Spinal muscular atrophy (SMA) is a severe neuromuscular disorder characterized by the degeneration of motor neurons in the spinal cord, and comprises a broad clinical spectrum. With the advent of new therapies (e.g. Nusinersen) for patients of all ages and disease stages, sensitive clinical measures are needed to detect slight changes in muscle force even in immobilized, severely affected patients often unable to move limbs. As for these patients, well-established outcome scales set out to evaluate motor function do not work properly, we propose measurement of maximum bite force which is able to detect subtle changes of bulbar function. Requirements for this approach are mentioned, challenges are discussed, and first insights from a pilot study are presented. Finally, a study design is proposed to evaluate the measurement of maximum bite force during the follow up of SMA-patients with and without a disease modifying therapy.